Tailoring Ordered Porous Carbon Embedded with Cu Clusters for High‐Energy and Long‐Lasting Phosphorus Anode. Issue 11 (13th January 2022) - Xiao, Jiajia; Cai, Zihe; Muhmood, Tahir; Hu, Xiaojun; Lin, Shengxuan; Hu, Xiaobin
Abstract: The natural insulating property and notorious pulverization of volume variation‐induced materials during cycling pares the electrochemical activity of red phosphorous (RP) for lithium/sodium‐ion batteries (LIBs/SIBs). To work out these issues, a tailored trimodal porous carbon support comprising highly ordered macropores and micro‐mesoporous walls embedded with copper (Cu) nanoclusters (Cu‐OMC) is proposed to confine RP. The construction of highly conductive copper–carbon wall facilitates fast electrons and ions transportation, while the interconnected and ordered porous structure not only creates enough space to resist the expansion effect of RP but also minimizes the ion diffusion length and enhances ion accessibility (the ion migration coefficient is ten times that of disordered porous carbon). Consequently, the resulting Cu‐OMC@RP anode delivers a high reversible capacity (2498.7 mAh g –1 at 0.3 C for LIBs; 2454.2 mAh g –1 at 0.1 C for SIBs), superb rate properties (824.7 mAh g –1 at 10 C for LIBs; 774.2 mAh g –1 at 5 C for SIBs), and outstanding cycling stability (an ultralow decay rate of 0.057% per cycle after 1000 cycles at 10 C for LIBs and 0.048% per cycle at 5 C over 500 cycles for SIBs). Abstract : A highly ordered porous carbon framework embedded with copper nanoclusters is tailored, and serves as the red phosphorus immobilizer for superior lithium and sodium storage. The unique structure not only facilitates the rapid lithium/sodium ions diffusion and electron transport but also effectively confines phosphorus and alleviates the volume expansion during cycling.